Fundamentals of Stereolithography, an Useful Tool for Diagnosis in Dentistry - Islas Ruiz DDS, Ma. del Socorro; Loyola Frías DDS, Miguel Ángel; Martínez Rider DDS, Ricardo; Pozos Guillén DDS, PhD, Amaury; Garrocho Rangel DDS, PhD, Arturo (Odovtos - International Journal of Dental Sciences, 2015)
Advancements in digital technology and imaging over the last 25 years have permitted the implementation of three-dimensional (3D) modeling protocols in Dentistry. The use of stereolithographic models has progressively replaced traditional milled models and x-rays in the management of craniofacial anomalies and in implant rehabilitation. Diverse advantages can be mentioned, including better visualization of complex anatomical structures and more precise and sophisticated pre-surgical planning, through a simulated insight of the procedures of interest. The aim of this review is to provide essential information about the different applications and limitations of stereolithography, addressed to those general dentists and dental students interested in gaining experience in the reconstructive surgery and implant placement fields.